A method for determining the local compressive bearing capacity of UHPC

By preparing the UHPC bonding test parts of the central channel and conduct a variety of tests, combined with qualitative analysis, propose the calculation formula for the UHPC bureau of different steel fiber parameters, solve the prediction of the UHPC bureau pressure bearing capacity in the existing technology Insufficient, achieve higher prediction accuracy and adaptability.

CN114878338BActive Publication Date: 2025-01-28CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111494683.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-08
Publication Date
2025-01-28
Estimated Expiration
2041-12-08

AI Technical Summary

Technical Problem

It is difficult for the prior art to accurately predict the bearing capacity of ultra-high performance concrete (UHPC) under local pressure conditions, especially considering the influence of steel fiber dosage, fiber aspect ratio and local pressure area ratio.

Method used

By preparing the UHPC bonded test parts of the central pores, local pressure, shaft heart pressure, and shaft heart anti -tensile test are performed, combined with qualitative analysis and bureau pressure test results, and proposes a shaft heart resistance strength, axis heart compressive strength strength The UHPC bureau pressure bearing capacity calculation formula of the UHPC bureau of the bureau's voltage area and the net area of ​​the bureau is calculated.

Benefits of technology

It provides the calculation formula of the UHPC bureau with a wide range of adaptation and high accuracy of the prediction accuracy. It can accurately predict the bureau's pressure bearing capacity under different steel fiber parameters and improve the reliability of structural design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114878338B_ABST
    Figure CN114878338B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for determining the local pressure bearing capacity of UHPC. The calculation formula of the local pressure bearing capacity of UHPC is: #imgabs0# where N u is the local pressure bearing capacity, f c is the axial compressive strength of UHPC, f t is the axial tensile strength of UHPC, α1, α2, α3 are unknown coefficients, c is a constant and c = 7; A b is the calculated bottom area under local pressure, A l is the local compression area of ​​concrete, A ln is the net area of ​​local concrete compression. For post-tensioned components, ln The area of ​​the hole and the groove is deducted from the method of the present invention. The prediction accuracy is higher.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for determining the local pressure bearing capacity of UHPC, that is, a method for determining the local pressure area of ​​UHPC with known local pressure load-local pressure bearing capacity. Background Art

[0002] Ultra-high performance concrete (UHPC), as a new type of cement-based composite material, has become a hot topic in recent years. Its steel fiber volume content is usually 1% to 3%. At present, domestic and foreign scholars' research on UHPC mainly focuses on the basic mechanical properties of structural components. [1-6] The application of UHPC materials to prestressed structures to form prestressed ultra-high performance concrete structures can achieve lightweight and increase the span of the structure. However, due to the existence of prestress, the local pressure problem in the end anchorage area of ​​small-sized structures is more prominent.

[0003] Domestic and foreign scholars have conducted a relatively systematic study on the local compressive properties of ordinary concrete under prestressing. [7-13] , and proposed the hoop strengthening theory, wedge splitting theory, tension-compression rod truss model and other methods to describe the local compression failure mechanism of concrete and calculate the local compression bearing capacity. Because UHPC does not contain coarse aggregate and contains steel fiber, its local compression failure form and local compression bearing capacity calculation formula should be significantly different from ordinary concrete that does not contain steel fiber but contains coarse aggregate. Due to the short development time of UHPC and the small number of prestressed UHPC structures, people's research on the local compressive bearing capacity of UHPC materials is relatively lacking. Zhang Lina

[14] studied the effect of local pressure area ratio on the local pressure performance of RPC materials and obtained the RPC local pressure strength influence coefficient β c However, the strength of the RPC specimen is not high and the local pressure area is relatively large, so the test results have certain limitations. [15-17] et al. found that reserved channels would significantly reduce the local compressive strength of reactive powder concrete, while indirect reinforcement could improve the restraint effect on the core reactive powder concrete, causing it to fail ductilely, and proposed a calculation formula for local compressive bearing capacity under different conditions. However, the RPC material in the experiment did not consider the effect of steel fiber aspect ratio and dosage.

[18] studied the effect of steel fiber content on the local compressive bearing capacity of RPC, but did not involve the aspect ratio, and the local compressive bearing capacity formula obtained did not include the tensile strength index.

[0004] The above UHPC (RPC is a typical UHPC) local compressive bearing capacity formulas obtained from existing research at home and abroad all borrow the expression form of the local compressive bearing capacity formula of ordinary concrete, and the basic strength index of the material in the formula only includes compressive strength. This is generally applicable to ordinary concrete with a roughly constant ratio of tensile strength to compressive strength. However, for UHPC, whose ratio of tensile strength to compressive strength varies significantly with different steel fiber parameters, the UHPC local compressive bearing capacity calculation formula that does not include the tensile strength index will be greatly limited in its scope of application.

[0005] In order to solve this problem, the literature

[19] uses the characteristic value of steel fiber content to consider the influence of the increase in tensile and compressive strength of UHPC materials due to fiber addition on its local compressive bearing capacity. This idea follows the idea of ​​the "Fiber Concrete Structure Code". However, since the basic strength indicators of material properties (axial compressive strength, axial tensile strength) do not directly affect the local compressive bearing capacity, the deviation between the calculated value of the theoretical formula of local compressive bearing capacity and the experimental value is slightly larger (coefficient of variation 0.19).

[19] Considering that UHPC structural design often includes tensile strength grades (labels) and compressive strength grades (labels) which can be proposed separately

[20]

[21] , the material strength index included in the local compressive bearing capacity formula of the present invention is directly the axial tensile strength and axial compressive strength index.

[0006] In addition, determining the local compressive bearing capacity of UHPC anchorages of post-tensioned tendons (beams) is also the basis for studying the local compressive bearing capacity of UHPC local compression zones with grid-type indirect reinforcement or spiral indirect reinforcement.

[0007] References

[0008] (1)Richard P,Cheyrezy M.Composition of reactive powder concretes[J].Cement&Concretce Research,1995,25(7):1501-1511.

[0009] (2)Larrard FD, Sedran T. Optimization of ultra-high-performanceconcrete by the use of a packing model[J]. Cement and Concrete Research, 1994, 24(6):997-1009.

[0010] (3)Doo-Yeol Yoo,Joo-Ha Lee,Young-Soo Yoon.Effect of fiber content onmechanical and fracture properties of ultra high performance fiber reinforcedcementitious composites[J].Composite Structures,2013,106.

[0011] (4) Kong Deyu, Jiang Shaojie, Liu Xinwei, Wang Dongliang. Preparation and performance research of ultra-high performance concrete[J]. Cement Engineering, 2017(01):83-86.

[0012] (5) Ju Yanzhong, Wang Dehong, Li Qiuchen, Jia Yuzhuo, Xiao Qi. Effect of steel fiber content on mechanical properties of reactive powder concrete[J]. Experimental Mechanics, 2011, 26(03): 254-260.

[0013] (6) Ju Yanzhong, Shao Anle, Wang Dehong. Research on factors affecting compressive strength of reactive powder concrete[J]. Concrete, 2017(01):130-132+136.

[0014] (7) Cai Shaohuai. Local compressive strength of concrete and reinforced concrete[J]. China Civil Engineering Journal, 1963(06):1-10+27.

[0015] (8) Cao Shengyuan, Yang Xikun, Niu Changren. Experimental study on the local axial compression failure and strength of concrete [J]. Journal of Harbin Institute of Civil Engineering, 1980(01):61-73.

[0016] (9) Cao Shengyuan, Yang Xikun, Niu Changren. Experimental study on local axial compression deformation of concrete[J]. Journal of Harbin Institute of Civil Engineering, 1980(01):74-84.

[0017] (10) Liu Yongyi, Cao Shengyuan, Yang Xikun, Wang Chuanzhi. Local compressive strength of concrete and reinforced concrete[J]. Building Structure, 1982, 12(4): 1-9.

[0018] (11) Liu Yongyi, Guan Jianguang, Wang Chuanzhi. Crack resistance calculation and reinforcement design of anchorage zone at the end of prestressed concrete structure [J]. Journal of Building Structures, 1983, 4(5): 11-22.

[0019] (12) Liu Yongyi, Guan Jianguang, Wang Chuanzhi. Local compressive strength and failure mechanism of concrete[J]. China Civil Engineering Journal, 1985(02):53-65.

[0020] (13) Cai Shaohuai, Xue Lihong. Local compressive strength of high-strength concrete[J]. China Civil Engineering Journal, 1994(05):52-61.

[0021] (14) Zhang Lina, Ba Fang, Zhang Wei. Experimental study on local compressive properties of reactive powder concrete[J]. Industrial Construction, 2009, 39(S1): 939-942.

[0022] (15) Zhou Wei, Hu Haibo. Analysis on local compression performance and bearing capacity of reactive powder concrete with reserved channels[J]. Engineering Mechanics, 2014, 31(07): 119-128.

[0023] (16) Zhou Wei, Zheng Wenzhong, Hu Haibo. Experimental study on local compression performance of reactive powder concrete confined by steel mesh[J]. Journal of Building Structures, 2013, 34(11): 141-150.

[0024] (17) Zhou Wei, Hu Haibo, Zheng Wenzhong. Experimental study on the bearing capacity of reactive powder concrete confined by high-strength spiral reinforcement under local compression[J]. China Civil Engineering Journal, 2014, 47(08): 63-72.

[0025] (18) Li Lifeng, Li Wenquan, Shi Xiongwei, Tang Jinliang, Chen Mingyu. Experimental study on the bearing capacity of reactive powder concrete under different curing conditions[J]. Journal of Chang'an University (Natural Science Edition), 2018, 38(02): 50-61.

[0026] (19) Qiu Minghong, Shao Xudong, Liu Qiongwei, et al. Calculation method of local compressive bearing capacity of UHPC[J]. Journal of Transportation Engineering, 2021, 21(4): 116-129.

[0027] (20) China Building Materials Association Standard “Basic Properties and Test Methods of Ultra-High Performance Concrete” (T / CBMF37-2018, T / CCPA 7-2018), jointly issued by China Building Materials Federation and China Concrete and Cement Products Association, released on November 7, 2018.

[0028] (21)Ultra-High Performance Fiber Reinforced Cement-based composites(UHPFRC)Construction material,dimensioning and application[s]MCS-EPFLLausanne,Switzerland,17April 2016.

[0029] (22) GB 50010-2010, Code for design of concrete structures[S]. Hu Haibo.

[0030] (23) Experimental study on the bearing capacity of post-tensioned reactive powder concrete under local compression[D]. Harbin Institute of Technology, 2012. Summary of the invention

[0031] The present invention aims to provide a method for determining the local compressive bearing capacity of UHPC, which has a wide range of applications (including different steel fiber dosages, different fiber aspect ratios, and different local pressure area ratios) and a UHPC local compressive bearing capacity calculation formula with higher prediction accuracy. The specific technical problem is to use the local compressive bearing capacity formula of ordinary concrete to calculate the UHPC strength influence coefficient β, taking into account the relatively independent characteristics of the tensile and compressive strengths of UHPC materials. c UHPC and UHPC local compressive strength improvement factor β l UHPC method of determination.

[0032] In order to achieve the above object, the technical solution adopted by the present invention is:

[0033] A method for determining the local pressure bearing capacity of UHPC. The calculation formula for the local pressure bearing capacity of UHPC is:

[0034]

[0035] Where N u is the local pressure bearing capacity, f c is the axial compressive strength of UHPC, f t is the axial tensile strength of UHPC, α1, α2, α3 are unknown coefficients, c is the tensile strength; A b is the calculated bottom area under local pressure, A l is the local compression area of ​​concrete, A ln is the net area of ​​local concrete compression. For post-tensioned components, ln Deduct the area of ​​the holes and grooves.

[0036] According to the embodiments of the present invention, the present invention can be further optimized. The following is the technical solution formed after optimization:

[0037] In one preferred embodiment, the method for determining the local compressive bearing capacity of UHPC of the present invention comprises the following steps:

[0038] Step 1: Prepare UHPC prism specimens with central holes and material property specimens of the same batch by setting the steel fiber aspect ratio, steel fiber content and local pressure area ratio as variables;

[0039] Step 2: Conduct local pressure, axial compression and axial tension tests on the specimen to obtain the corresponding load-displacement curve and UHPC axial compressive strength fc and UHPC axial tensile strength f t ;

[0040] Step 3: The calculation formula for the local pressure bearing capacity of UHPC is

[0041]

[0042] Where: β c UHPC is the UHPC strength influence coefficient; β l UHPC is the UHPC strength improvement factor; f c A is the axial compressive strength of concrete; ln is the net area of ​​local concrete compression;

[0043] Step 4: Based on the analysis of the local pressure failure morphology and characteristics, three assumptions are given:

[0044] ① Assuming the concrete strength influence coefficient β c UHPC It is linearly related to tensile strength;

[0045] ② Assuming that the concrete strength improvement coefficient β under UHPC local pressure l UHPC It is linearly related to the square root of the local pressure area ratio;

[0046] ③ Assuming that the local pressure failure form of UHPC is strict wedge splitting failure, it follows the hoop strengthening theory;

[0047] Based on the assumption, the expression of the concrete strength influence coefficient is proposed:

[0048]

[0049] Based on the assumption, the expression of concrete strength improvement coefficient is proposed:

[0050]

[0051] Where: β c UHPC is the influence coefficient of concrete strength under local pressure of UHPC, f t A is the axial tensile strength of UHPC; b A is the calculated bottom area under local pressure; l is the local compression area of ​​concrete;

[0052] Substituting equations (2) and (3) into equation (1), we can obtain the calculation expression of UHPC local compressive bearing capacity:

[0053]

[0054] Step 5: Substitute the test results and related parameters of each specimen into formula (4) to determine the various coefficients by regression.

[0055] In one preferred embodiment, the specific process of regressing to determine each coefficient is as follows:

[0056] ① For each specimen, the above formula (4) can be obtained, thus obtaining several nonlinear equations with unknown coefficients α1, α2, and α3;

[0057] ② Using the principle of least squares method, input several nonlinear equations and solve the approximate solutions of α1, α2, and α3, and finally substitute them into equations (2), (3), and (4).

[0058] In one preferred embodiment, the aspect ratio of the UHPC prism is not less than 2.

[0059] In one preferred embodiment, c = 6-8 MPa, preferably 7 MPa; ft = 7 MPa, β c UHPC Take 1.

[0060] In one preferred embodiment, α1=0.04-0.06, preferably 0.05007.

[0061] In one preferred embodiment, α2=0.0009-0.0011, preferably 0.00105.

[0062] α3=-0.00011 to -0.00015, preferably -0.00013.

[0063] The present invention is further described below:

[0064] By combining qualitative analysis with quantitative calculation of the results obtained from the local pressure test (see Figure 1 for the test device), a calculation formula for the local pressure bearing capacity of UHPC with a wide range of applications and high prediction accuracy was obtained. This formula can be used to verify the local pressure bearing capacity under the post-tensioned prestressed anchor or to determine the plane area of ​​the anchor pad, etc.

[0065] The specific steps to obtain the calculation formula for the local compressive bearing capacity of UHPC with a wide range of applications and high prediction accuracy are as follows (see Figure 2 ).

[0066] Step 1: UHPC prism specimens with central channels (18 in total) and material properties specimens of the same batch were prepared by setting the steel fiber aspect ratio, steel fiber content and local pressure area ratio as variables. It is worth noting that the study shows that when the concentrated pressure transmission distance is equal to the length of the long side of the cross section of the component, the longitudinal compressive stress is basically uniformly distributed; when the aspect ratio of ordinary concrete specimens is not less than 2, the local pressure will form a wedge-shaped body, so the specifications of the UHPC prism should meet the aspect ratio of not less than 2, so as to comply with the wedge splitting theory.

[0067] Step 2: Conduct local pressure, axial compression and axial tension tests on the specimen to obtain the corresponding load-displacement curve and UHPC axial compressive strength f c and UHPC axial tensile strength f t When conducting local pressure test, the local pressure area ratio between the local pressure steel pad and the UHPC prism should be determined based on the principle of "concentricity and symmetry".

[0068] Step 3: The calculation formula of the local compressive bearing capacity of UHPC adopts the "Code for Design of Concrete Structures" (GB50010-2010)

[22] The calculation formula for the local compressive bearing capacity of ordinary concrete is given in the form of qualitative analysis, namely

[0069]

[0070] Where: β c UHPC β is the UHPC strength influence coefficient. Considering that the local compression failure form of UHPC is mainly wedge splitting failure, it is greatly affected by the axial tensile strength of the material; l UHPC is the UHPC strength improvement coefficient, and the influence of the local pressure area ratio needs to be considered; f c A is the axial compressive strength of concrete; ln is the net local compressive area of ​​concrete,

[0071] Step 4: Analyze the local pressure failure morphology and characteristics (see Figure 3 , Figure 4 , Figure 5 ) based on (qualitative analysis), three assumptions are given:

[0072] ① Assuming the concrete strength influence coefficient β c UHPC It is linearly related to tensile strength;

[0073] ② Assuming that the concrete strength improvement coefficient β under UHPC local pressure l UHPC It is linearly related to the square root of the local pressure area ratio;

[0074] ③ It is assumed that the local compression failure form of UHPC is a strict wedge splitting failure, following the hoop strengthening theory.

[0075] Based on the assumption, the expression of the concrete strength influence coefficient is proposed:

[0076]

[0077] Based on the assumption, the expression of concrete strength improvement coefficient is proposed:

[0078]

[0079] Where: β c UHPC is the influence coefficient of concrete strength under local pressure of UHPC, and takes 1 when the tensile strength is 7MPa, f t A is the axial tensile strength of UHPC; b A is the calculated bottom area of ​​local compression, determined in accordance with Article 6.6.2 of the Code for Design of Concrete Structures (GB 50010-2010); l is the local compression area of ​​concrete; α1, α2, α3 are unknown coefficients.

[0080] Substituting equations (2) and (3) into equation (1), we can obtain the calculation expression of UHPC local compressive bearing capacity:

[0081]

[0082] Step 5: Substitute the test results and related parameters of each specimen into formula (4) to regress and determine each coefficient (quantitative calculation). The specific process is: ① For each specimen, the above formula (4) can be obtained, so that several nonlinear equations with unknown coefficients α1, α2, and α3 can be obtained. The more specimens there are, the more accurate the data is. Obviously, it is necessary to solve the contradictory equations; ② Using the principle of least squares method, through the mathematical software MatLab, several nonlinear equations are input to solve the approximate solutions of α1, α2, and α3, and finally substitute them into formulas (2), (3), and (4).

[0083] Compared with the prior art, the beneficial effects of the present invention are as follows: the determination method of the present invention is based on the local pressure test results of 18 UHPC prisms with central channels of different steel fiber aspect ratios, steel fiber dosages, and local pressure area ratios, and deeply grasps the distinct characteristics of UHPC tensile strength and compressive strength being relatively independent, which is different from the change of ordinary concrete in a certain proportion. On the basis of the existing concrete local pressure bearing capacity formula, a method including axial tensile strength, axial compressive strength, local pressure area ratio and local net pressure area is proposed, which provides a method for determining the local pressure area or verifying the local pressure bearing capacity. The determination method of the UHPC strength influence coefficient in the UHPC local pressure bearing capacity calculation formula is used.

[0084] The UHPC local pressure bearing capacity calculation formula obtained by the present invention has a wide range of applications and high prediction accuracy. The formula includes five parameters of UHPC axial tensile strength, axial compressive strength, local pressure area ratio, net local pressure area and local pressure bearing capacity. If four parameters are known (or selected), the other one can be determined. The formula is applicable to UHPC with a steel fiber volume content of 1% to 3% or even a larger range of content. It is more convenient to use for designers and has higher accuracy.

[0085] Experiments show that the present invention has high accuracy and wide adaptability for predicting the limited bearing capacity of UHPC with a steel fiber volume content of 1% to 3%, or even a larger range of steel fiber content. BRIEF DESCRIPTION OF THE DRAWINGS

[0086] Figure 1a is a schematic diagram of a loading and measuring device of the present invention;

[0087] Figure 1b is a top view of the arrangement of the displacement meter of the present invention;

[0088] Figure 1c is a schematic diagram of deformation measurement of the present invention;

[0089] Figure 2 It is a flow chart of the scheme of the present invention;

[0090] Figure 3 are the failure morphology diagrams of the specimens (6 of them are listed, and the others are similar), among which (a) is the failure morphology diagram of the S3 specimen, (b) is the failure morphology diagram of the S6 specimen, (c) is the failure morphology diagram of the S9 specimen, (d) is the failure morphology diagram of the L3 specimen, (e) is the failure morphology diagram of the L6 specimen, and (f) is the failure morphology diagram of the L9 specimen;

[0091] Figure 4 is the crack development diagram of the specimen (after stopping loading) (6 specimens are given, and the other specimens are similar), where (a) is the top view and the development diagram in the front, right, back and left directions of the S3 specimen, (b) is the top view and the development diagram in the front, right, back and left directions of the S6 specimen, (c) is the top view and the development diagram in the front, right, back and left directions of the S9 specimen, (d) is the top view and the development diagram in the front, right, back and left directions of the L3 specimen, (e) is the top view and the development diagram in the front, right, back and left directions of the L6 specimen, (f) is the top view and the development diagram in the front, right, back and left directions of the L9 specimen; Note: The numbers represent the crack width; the shaded part represents the peeling of the concrete surface;

[0092] Figure 5 The crack characteristics of the specimen of the present invention after the loading stops (after destruction) are (similar) wherein (a) is a schematic diagram of the top surface; and (b) is a schematic diagram of the side surface.

[0093] In the figure

[0094] 1,2,3,4,5,6,7-sensors; 101-crossbeam; 102-steel sheet; 103-vertical axis; 104-magnetic base; 105-top plate; 106-pressure plate; 107-bottom plate; 108-test piece. DETAILED DESCRIPTION

[0095] The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict. For the convenience of description, if the words "upper", "lower", "left" and "right" appear in the following, they only indicate that the upper, lower, left and right directions are consistent with the drawings themselves, and do not limit the structure.

[0096] A method for determining the local compressive bearing capacity of UHPC comprises the following steps:

[0097] Step 1: First, 18 UHPC prism specimens with central holes and UHPC axial compression and axial tension specimens of the same batch were prepared by considering the steel fiber content, steel fiber aspect ratio and local pressure area ratio as the key factors of UHPC local pressure. The specifications of the UHPC prism specimens are 150mm×150mm×300mm. Considering the presence of prestressed pipes under the anchor block during actual tensioning, a circular hole with a diameter of 40mm is reserved in the center of the cross section of all specimens to simulate the actual stress state. The specimen numbers and parameter selections are shown in Table 1.

[0098] Table 1 Test parameters

[0099]

[0100] Note: S / L are steel fiber lengths 65 / 80mm respectively.

[0101] Step 2: 18 UHPC prism specimens were subjected to local pressure tests. The local pressure rigid pads were placed on the UHPC prism specimens according to the principle of “concentricity and symmetry” and loaded by a microcomputer-controlled electro-hydraulic servo pressure testing machine. The loading diagram is shown in Figure 1. The cracking load and ultimate load of the 18 specimens are shown in Table 2.

[0102] Table 2 Cracking load and ultimate load

[0103]

[0104] Note: Pcr represents cracking load and Pu represents ultimate load.

[0105] The test results of basic mechanical properties of the same batch of UHPC materials are shown in Table 3.

[0106] Table 3 UHPC mechanical properties

[0107]

[0108]

[0109] Note: cu is the compressive strength of UHPC cube, f c is the axial compressive strength of UHPC, f t is the axial tensile strength of UHPC.

[0110] Step 3: The calculation formula for the local compressive bearing capacity of UHPC adopts the calculation formula for the local compressive bearing capacity of ordinary concrete given in the Code for Design of Concrete Structures (GB50010-2010), namely

[0111]

[0112] Step 4: Considering the key factors of UHPC local pressure failure, namely, the local pressure area ratio, the tensile and compressive effects of UHPC, and three basic assumptions, the expression of the influence coefficient of concrete strength is given:

[0113]

[0114] The expression for the concrete strength improvement coefficient is given as:

[0115]

[0116] Substituting equations (2) and (3) into equation (1), we can obtain the calculation expression of UHPC local compressive bearing capacity:

[0117]

[0118] Step 5: Determine the coefficient. u 、f t , A b , A l 、f c , A ln Substituting (4) into 18 nonlinear equations with only three parameters, namely α1, α2, and α3, the approximate solutions of these 18 nonlinear equations are obtained by MatLab, and the variables are shown in Table 4 below.

[0119] Table 4 Summary of data of each variable

[0120]

[0121]

[0122] The MatLab programming procedure is as follows:

[0123] clear all;

[0124] clc;

[0125] load data.txt;

[0126] xdata=data(:,2:5);

[0127] ydata=data(:,1);

[0128] m = length(ydata);

[0129] options=optimset('MaxIter',1000,'TolFun',1e-22,'TolX',1e-22);

[0130] myfun=@(beta,x)(1+(xdata(:,1)-7).*(beta(1)).*(beta(2)).*sqrt(xdata(:,2))+beta(3)).

[0131] *xdata(:,3).*xdata(:,4);

[0132] beta=nlinfit(xdata,ydata,myfun,[0.014,0.0011,-0.0001],options)

[0133] Vpa(beta)

[0134] Finally, the approximate solutions of α1, α2, and α3 are 0.05007, 0.00105, and -0.00013, respectively. Substituting them into (2) and (3), we can get the expressions of concrete strength influence coefficient and concrete strength improvement coefficient:

[0135]

[0136]

[0137] Substituting equations (5) and (6) into equation (1), we can obtain the expression of UHPC local compressive bearing capacity:

[0138]

[0139] The following is an illustration of the effective effects of the present invention by comparing the test results (conducted by the inventor) on which the present invention is based, the test results of document

[23] , the results of the formula obtained by the present invention, and the results obtained in document

[19] .

[0140] The test scheme of the local pressure test of the present invention and the properties of UHPC materials

[0141] (1) Specimen size and parameter setting

[0142] The local pressure test uses prismatic specimens with a size of 150mm×150mm×300mm. Considering the presence of prestressed pipes under the anchor block during actual tensioning, a circular hole with a diameter of 40mm is reserved in the center of the cross section of all specimens to simulate the actual stress state. Three parameters are selected in the test, namely, steel fiber aspect ratio, steel fiber content, and local pressure area ratio.

[0143] Taking into account that straight copper-plated steel fibers are easy to process and have a wide range of applications, the steel fibers selected for the test were all straight copper-plated steel fibers, with aspect ratios of 65 (denoted as S group) and 80 (denoted as L group) (both with diameters of 0.2 mm and lengths of 13 mm and 16 mm respectively); the steel fiber content was selected at 1%, 2%, and 3%.

[0144] Considering that small local pressure area ratios are often used in actual projects, and the significant improvement in UHPC strength will also make the structure smaller, the diameter d of the circular steel pressure plate in the local pressure test is taken as 90mm, 100mm, and 110mm, and the pressure plate thickness is 3cm. Therefore, the local pressure area ratio of the specimen (cross-sectional area / local pressure area) A b / A l They are 3.537, 2.864 and 2.367 respectively. The test parameters are shown in Table 1.

[0145] (2) UHPC material properties

[0146] Two types of specimens were made in the same batch as the local pressure specimens, namely, a cubic specimen with a side length of 100 mm and a prism specimen with a length × width × height of 150 mm × 150 mm × 300 mm (3 pieces), which were used to test the mechanical properties of UHPC materials. The test results are shown in Table 3.

[0147] (3) Test methods

[0148] The test loading device uses a microcomputer-controlled electro-hydraulic servo pressure testing machine, and selects displacement loading with a loading speed of 0.02 mm / min to facilitate observation of crack development; in order to ensure uniform loading, a layer of fine sand is laid between the specimen and the pressure plate and the bottom plate of the press. Before loading, the specimen needs to be preloaded 1 to 2 times, and the preload value is about 20% of the estimated failure load of the specimen.

[0149] The load corresponding to the first visible crack is used as the cracking load, and the displayed load peak is used as the ultimate load P. u In the test, displacement meters were used to measure deformation. The displacement meters had an accuracy of 0.001 mm and were fixed on the surface of the press through magnetic bases. The layout is shown in Figure 1.

[0150] As shown in Figure 1, displacement gauge No. 1 is pointing vertically to the top plate of the press, and the measured value is the vertical compression of the core of the specimen Δ cc ; The displacement gauges No. 2 and No. 3 point to the steel sheet attached to the top surface of the specimen, and the measured value is the vertical compression of the periphery of the specimen Δ c ; Displacement gauges 4 to 7 are respectively pointed vertically to the center of the four sides of the specimen to measure the lateral expansion deformation of the side of the specimen Δ ce The local relative indentation value Δ cs , it can be seen from the deformation measurement schematic diagram in Figure 1 that the local relative indentation value Δ cs =Δ cc -Δ c .

[0151] Comparative Example 1: Experimental scheme of local pressure test in reference

[23] and UHPC material properties

[0152] (1) Specimen size and parameter setting

[0153] The local pressure test adopts prismatic specimens with the size of 200mm×200mm×400mm. Three parameters are selected for the specimens, namely the reserved channel diameter d, the steel fiber content and the local pressure area ratio.

[0154] A circular hole that runs through the entire height (400mm direction) is reserved at the center of the specimen cross section, and the diameters d of the hole are 20mm, 32mm, and 50mm respectively. b / A l Three different levels were selected: 4, 3.025 and 2.041, and three rectangular pressure plates with different side lengths were used, with side lengths a of 100 mm, 115 mm and 140 mm respectively. The specimen group with steel fiber was numbered RPC-sh, and the steel fiber volume content was 2%. The specimen parameters are shown in Table 5.

[0155] Table 5 Experimental parameters of RPC-sh group

[0156]

[0157] (2) RPC material properties

[0158] Under the same conditions as the local pressure test pieces, a cubic test piece with a side length of 100 mm and a prism test piece with a size of 150 mm × 150 mm × 300 mm were made. The mechanical properties test of RPC was carried out before the local pressure test, and the mechanical properties of RPC are shown in Table 6.

[0159] Table 6 RPC performance indicators

[0160]

[0161] (3) Test methods

[0162] The experimental loading device uses a YEW-5000 hydraulic pressure testing machine, which adopts graded loading, with each level of load not exceeding 10% of the estimated failure load and holding the load for 10 minutes. In order to ensure uniform loading, a layer of fine sand is laid between the specimen and the pressure plate and the bottom plate of the press. The specimen needs to be preloaded 1 to 2 times before loading, and the preload value is about 20% of the estimated failure load of the specimen. The load corresponding to the first visible crack is the cracking load, and the peak value of the test load is the ultimate load.

[0163] The deformation of the specimens under local pressure load is respectively the depression of the pressure plate (i.e. the depression of the wedge relative to the outer matrix) Δ cs , vertical compression deformation of core matrix Δ cc , the overall vertical compression deformation of the specimen Δ c , lateral expansion deformation Δ ce The layout of the displacement meter is similar to that in Figure 1.

[0164] Effective effect test of the formula obtained by the present invention

[0165] (1) Verification based on the inventor’s UHPC local compressive bearing capacity test results

[0166] Table 7 gives the actual measured values ​​of the local pressure bearing capacity of the inventors The calculated value of the local compressive bearing capacity formula obtained by the inventor Reference

[19] suggests that the calculation value of the local compressive bearing capacity formula is and the corresponding ratios.

[0167] Table 7 Comparison of local compressive bearing capacity of specimens

[0168]

[0169] The 18 specimens in Table 7 are numbered as follows: The average value The standard deviation is σ x =0.053,σ y =0.075, the coefficient of variation is δ x =5.28%,δ y =8.44%. The results show that the prediction accuracy of the formula obtained by the present invention is higher than that of the formula obtained in the literature

[19] .

[0170] (2) Verification of the local compressive bearing capacity test results of RPC-sh (i.e., UHPC) based on reference

[23] The measured values ​​of the local compressive bearing capacity of the RPC-sh (i.e., UHPC) group in reference

[23] and the calculated values ​​according to formula (7) obtained in the present invention are shown in Table 8.

[0171] Table 8 Local compressive bearing capacity of RPC-sh specimens

[0172]

[0173] The 9 specimen data in Table 8 are numbered. The average value is The standard deviation is σ2 = 0.110, and the coefficient of variation is δ2 = 10.07%. The calculated value of the formula obtained by the present invention is consistent with the measured value with high accuracy.

[0174] Reference

[23] did not provide the length and diameter of the steel fibers used, so it was not possible to calculate the local compressive bearing capacity of the RPC-sh group specimens using the formula suggested in reference

[19] .

[0175] From the above analysis, it can be seen that the present invention has high accuracy and wide adaptability for predicting the limited bearing capacity of UHPC with a steel fiber volume content of 1% to 3%, or even a larger range of steel fiber content.

[0176] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the embodiments made by those skilled in the art fall within the scope defined by the claims attached to the present invention.

Claims

1. A method for determining the local compressive bearing capacity of UHP C, characterized in that: The determination method comprises the following steps: Step 1: Prepare UHPC prism specimens with central holes and material property specimens of the same batch by setting the steel fiber aspect ratio, steel fiber content and local pressure area ratio as variables; Step 2: Conduct local pressure, axial compression and axial tension tests on the specimen to obtain the corresponding load-displacement curve and UHP C axial compressive strength f c and UHPC axial tensile strength f t ; Step 3: The calculation formula for the local pressure bearing capacity of UHP C is: Where: N u is the local compressive bearing capacity, β c UHPC is the UHPC strength influence coefficient; β l UHPC is the UHPC strength improvement factor; f c A is the axial compressive strength of concrete; ln is the net area of ​​local concrete compression. For post-tensioned components, ln Deduct the area of ​​the holes and grooves; Step 4: Based on the analysis of the local pressure failure morphology and characteristics, three assumptions are given: ① Assuming the concrete strength influence coefficient β c UHPC It is linearly related to tensile strength; ② Assuming that the concrete strength improvement coefficient β under UHPC local pressure l UHPC It is linearly related to the square root of the local pressure area ratio; ③ Assuming that the local pressure failure form of UHPC is strict wedge splitting failure, it follows the hoop strengthening theory; Based on the assumption, the expression of the concrete strength influence coefficient is proposed: Based on the assumption, the expression of concrete strength improvement coefficient is proposed: Where: β c UHPC is the influence coefficient of concrete strength under local pressure of UHPC, f t A is the axial tensile strength of UHPC; b A is the calculated bottom area under local pressure; l is the local compression area of ​​concrete; Substituting equations (2) and (3) into equation (1), we can obtain the calculation expression of UHPC local compressive bearing capacity: α1, α2, α3 are unknown coefficients, c is the tensile strength; Step 5: Substitute the test results and related parameters of each specimen into formula (4) to determine the various coefficients by regression.

2. The method for determining the local compressive bearing capacity of UHPC according to claim 1, characterized in that: The specific process of regression to determine each coefficient is: ① For each specimen, the above formula (4) can be obtained, thus obtaining several nonlinear equations with unknown coefficients α1, α2, and α3; ② Using the principle of least squares method, input several nonlinear equations and solve the approximate solutions of α1, α2, and α3, and finally substitute them into equations (2), (3), and (4).

3. The method for determining the local compressive bearing capacity of UHPC according to claim 1, characterized in that: The aspect ratio of the UHPC prism is not less than 2.

4. The method for determining the local compressive bearing capacity of UHPC according to any one of claims 1 to 3, characterized in that: c=6~8MPa.

5. The method for determining the local compressive bearing capacity of UHPC according to claim 4, characterized in that: c=7MPa;ft=7MPaβ c UHPC Take 1.

6. The method for determining the local compressive bearing capacity of UHPC according to any one of claims 1 to 3, characterized in that: α1=0.04~0.06。 7. The method for determining the local compressive bearing capacity of UHPC according to claim 6, characterized in that: α1=0.05007。 8. The method for determining the local compressive bearing capacity of UHPC according to any one of claims 1 to 3, characterized in that: α2=0.0009~0.0011。 9. The method for determining the local compressive bearing capacity of UHPC according to claim 8, characterized in that: α2=0.00105。 10. The method for determining the local compressive bearing capacity of UHPC according to any one of claims 1 to 3, characterized in that: α3=-0.00011~-0.00015。 11. The method for determining the local compressive bearing capacity of UHPC according to claim 10, characterized in that: α3=-0.00013。